Nursing diagnoses in elderly people with diabetes mellitus according to Orem's Self-Care Theory - Francielle Renata Danielli Martins Marques; Patrícia Bossolani Charlo; Grazieli Adrieli Rodrigues Pires; Cremilde Aparecida Trindade Radovanovic; Lígia Carreira; Maria Aparecida Salci (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To identify nursing diagnoses and conditioning factors of self-care in older adults with diabetes mellitus, in the light of Orem's Theory of Self-Care. Methods: Exploratory, descriptive study with a qualitative approach, conducted with the theoretical framework of Orem's Theory of Self-Care. It was developed with 12 older people with diabetes, in a country's southern municipality, between October and November 2019. For data collection, it was used individual interviews and focus groups. The data was submitted to thematic and content analysis directed to taxonomy II of NANDA International. Results: Twenty nursing diagnoses related to universal self-care requirements and health deviations were identified. All diagnoses were anchored in the supportive-education nursing system. Final considerations: The development of the disease and the consequences of chronic hyperglycemia were poorly recognized by the elderly, interfering with low adherence to self-care practices and disease control.